2021
DOI: 10.1155/2021/9601012
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive Deionization for the Removal of Paraquat Herbicide from Aqueous Solution

Abstract: In comparison to other conventional methods like adsorption and reverse osmosis (RO), capacitive deionization (CDI) has only been investigated extensively for the removal of inorganic pollutants from water, demonstrating limited practicality. Herein, the study investigated the use of CDI for the removal of paraquat (PQ) herbicide from water by using commercial activated carbon (AC) electrodes. The CDI performance was examined as a function of the initial PQ concentration, applied voltage, flowrate, treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…CDI technology has also been used for removal of textile dyes from industrial wastewater with removal efficiency of 98% (Alfredy et al, 2021). Porada et al (2012) have reported higher adsorption capacity of activated carbon electrodes in the cell voltage range of 1.2 -1.4 V.…”
Section: Technology Has Also Been Used For Removal Of Textile Dyes Fr...mentioning
confidence: 99%
See 1 more Smart Citation
“…CDI technology has also been used for removal of textile dyes from industrial wastewater with removal efficiency of 98% (Alfredy et al, 2021). Porada et al (2012) have reported higher adsorption capacity of activated carbon electrodes in the cell voltage range of 1.2 -1.4 V.…”
Section: Technology Has Also Been Used For Removal Of Textile Dyes Fr...mentioning
confidence: 99%
“…CDI technology has also been used for removal of textile dyes from industrial wastewater with removal efficiency of 98% (Alfredy et al., 2021). Porada et al.…”
Section: Introductionmentioning
confidence: 99%